EFFICIENCY OF THE NEW MEDICATION OF FS-1 IN THE TREATMENT OF EXPERIMENTAL TUBERCULOSIS - M. E. Kulmanov; B. F. Kerimzhanova; L. N. Chernousova; I. V. Bocharova; L. N. Lepekha; A. I. Il'in (Туберкулез и болезни лёгких)
In vitro studies have proved the anti-tuberculosis eect of FS-1 medication both against susceptible strain of M. tuberculosis H37Rv, and the strain of M. tuberculosis MS-115 with multiple drug resistance.Conducted in vivo studies on guinea pigs infected with the pathogenic culture of human tuberculosis (strain of H37Rv), have shown that FS-1 provides expressed anti-inflammatory action on the course of experimental tuberculosis.